On a first-name basis: Englishization and naming in Flanders - Zenner, Eline; Marzo, Stefania (Complutense Journal of English Studies, 2015)
Following and contributing to the ongoing shift from more structuralist, system-oriented to more pragmatic, socio-cultural oriented anglicism research, this paper verifies to what extent the global spread of English affects naming patterns in Flanders. To this end, a diachronic database of first names is constructed, containing the top 75 most popular boy and girl names from 2005 until 2014. In a first step, the etymological background of these names is documented and the evolution in popularity of the English names in the database is tracked. Results reveal no notable surge in the preference for English names. This paper complements these database-driven results with an experimental study, aiming to show how associations through referents are in this case more telling than associations through phonological form (here based on etymology). Focusing on the socio-cultural background of first names in general and of Anglo-American pop culture in particular, the second part of the study specifically reports on results from a survey where participants are asked to name the first three celebrities that leap to mind when hearing a certain first name (e.g. Lana, triggering the response Del Rey). Very clear associations are found between certain first names and specific celebrities from Anglo-American pop culture. Linking back to marketing research and the social turn in onomastics, we will discuss how these celebrities might function as referees, and how social stereotypes surrounding these referees are metonymically attached to their first names. Similar to the country-of-origin-effect in marketing, these metonymical links could very well be the reason why parents select specific “celebrity names”. Although further attitudinal research is needed, this paper supports the importance of including socio-cultural parameters when conducting onomastic research.